Anatomical and Agronomic Responses of Arabica Coffee Seedlings (Coffea arabica) to Addition of Nitrogen - Distiana Wulanjari; Ketut Anom Wijaya; Budi Kriswanto (Universitas Khairun, 2023)
The role of nitrogen in plant growth is well known, but there have been few studies on the response of nitrogen fertilizers to changes in plant anatomy and agronomy. This study aims to observe the response of the tissue and organs of arabica coffee seedlings to adding nitrogen. Nitrogen is used in the urea fertilizer form. This research used a single factor of CRD with five replications. 4 levels were tried without urea fertilizer as a control (N1), dosage of urea fertilizer 15 g urea.plant-1 is equivalent to 6,9 g of nitrogen (N2), dosage of urea fertilizer 30 urea.plant-1 is equivalent to 13,8 g of nitrogen (N3), and dosage of urea fertilizer urea.plant-1 is equivalent to 20,7 g of nitrogen (N4). After application, the plants are incubated for 30 days to allow time for the fertilizer to be absorbed by the plants. The analysis result stated that the chlorophyll content was very significantly different, while other agronomic variables were not significantly different. Less adaptation period was thought to be the cause of the various agronomic variables being not significantly different. This is reinforced by the response that arises in plant tissue. The addition of urea fertilizer responded to the thickness of the mesophyll tissue, the size of the epidermal cells, and the regularity of the lower epidermal cells. The result of this research concluded that the response of plants to the treatment had not yet reached the organ level but was still at the tissue level.